If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y = 3(0) + 11(0) + -4 Multiply 3 * 0 y = 0 + 11(0) + -4 Anything times zero is zero. y = 0 + 11(0) + -4 Multiply 11 * 0 y = 0 + 0 + -4 Anything times zero is zero. y = 0 + 0 + -4 Combine like terms: 0 + 0 = 0 y = 0 + -4 y = -4 Solving y = -4 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Simplifying y = -4
| P+28=8 | | v/15=-4 | | 12ax+20bx+32cx= | | 13x+14x=15x-1 | | 7=v/4 | | K*18=90 | | 6n=-3n-27 | | 3x^2+11x-4=-4x-4 | | (9x-1)+4x=95 | | x+90-15=210 | | 80+(80-x)=90 | | 19x+5x+6x= | | 6v^7+22v^6+20v^5= | | X/8-20=-6 | | 3+15-5=2 | | m/19=4 | | 3x+3x+2=2x+2x+4 | | 0.09Xx=70.22 | | 48+(x-35)=90 | | -6(v+3)+4v+6=7v+7 | | 7(x-14)=49 | | 2.3=a/5 | | 10-3(m-2)=1 | | 12+(x+25)=90 | | 9/12=x/100 | | x+2x+2=2x+5 | | 5(x+60)=900 | | 78-132= | | K-1/3=22/3 | | 5x+15=41 | | 12=g+9-3 | | 4x+x+3=2x+6 |